On the Generalized Thermoelasticity Problem for an Infinite Fibre-Reinforced Thick Plate under Initial Stress (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, the generalized thermoelasticity problem for an infinitefiber-reinforced transversely-isotropic thick plate subjected to initialstress is solved. The lower surface of the plate rests on a rigid foundationand temperature while the upper surface is thermally insulated with prescribedsurface loading. The normal mode analysis is used to obtain the analyticalexpressions for the displacements, stresses and temperature distributions.The problem has been solved analytically using the generalized thermoelasticitytheory of dual-phase-lags. Effect of phase-lags, reinforcement and initial stresson the field quantities is shown graphically. The results due to the coupledthermoelasticity theory, Lord and Shulman's theory, and Green and Naghdi's theoryhave been derived as limiting cases. The graphs illustrated that the initial stress,the reinforcement and phase-lags have great effects on the distributions of the field quantities.